METHOD OF SELF-PRIMING AS A WAY TO INCREASE OF PRODUCTION EFFICIENCY OF THE HIGH QUALITY CASTING OF ALUMINIUM ALLOYS - M. A. Sadoha; N. E. Bondarik (Литьë и металлургия)
It is shown that the method of filling allows to increase considerably the lay-out of non-defective casting at production of stretched castings as compared to casting in stationary chill mold.